A novel magnetic heterojunction photocatalyst TiO2/SrFe12O19: synthesis strategy, photocatalytic activity, and unprecedented migration mechanism of photoexcited charge carrier. (29th July 2018) - Xie, Taiping; Xu, Longjun; Liu, Chenglun; Zhang, Xiaodong
ABSTRACT: A novel magnetic heterojunction photocatalyst TiO2 /SrFe12 O19 was synthesized from self-made strontium carbonate and Tetra-n-butyl Titanate by ultrasound technique. Acting as magnetic substrate, multifunctional strontium ferrite (SrFe12 O19 ) played an important role in the magnetic heterojunction photocatalyst system. On the one hand, as n-type semiconductors, SrFe12 O19 was in contact with TiO2, and a heterojunction was generated. On the other hand, as a hard-magnetic material SrFe12 O19 can produce a stable magnetic field. This facilitates the recovery of photocatalyst from reaction solution with an extra magnet. More important, the stable magnetic field stemming from SrFe12 O19 can promote separation between photo-induced electrons and holes and enhance the quantum efficiency for TiO2 . In this work, we proposed an unprecedented migration mechanism of photoexcited charge carriers. It is hope to provide new insight into photocatalytic mechanism for extending our understanding.